HUBUNGAN AKTIVITAS BACA DENGAN KEJADIAN KELAINAN REFRAKSI PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 5 KENDARI - Nurul Aulia Gaus; Nevita Yonnia Ayu; Adius Kusnan (NHM PRESS, 2021)
Refractive disorders or ametropia are disorders of the refraction of light in the eye so that the light is not focused on the retina or yellow spots, but in front or behind the yellow spots or not located at a single focal point. This disorder is known as myopia, hypermetropia, and astigmatism. In 2019 the WHO said, globally, it was estimated that at least 2.2 billion people had visual impairment or blindness, of whom at least 1 billion had preventable or unrevised vision problems. This research is an analytic type of study with a case-control approach conducted at SMP Negeri 5 Kendari. The sample of this study was 184 respondents consisting of 92 respondents for each case and control. The sampling calculation is using the Slovin formula. The data compilation is collected using a questionnaire. Data were analyzed using the Chi-square statistical test and the Odds Ratio. The results of this research indicate that there is a connection between reading activity time and refractive abnormalities with a p-value of 0,000 and POR = 9,347. There is also a connection between reading activity distance and the occurrence of anomalies with a p-value of 0,000 and POR = 18,050. There is a correlation between reading activity time and refractive abnormalities in students of SMP Negeri 5 Kendari. Also, there is a correlation between reading activity distance in students of SMP Negeri 5 Kendari.